Quality of Life in Breast Cancer Patients: The Moderator Role of Family Stress - Pereira, M.Graça; Paredes, Ana Cristina; Nabiço, Rui; Ribeiro, Catarina; Ferreira, Gabriela (Anales de Psicología / Annals of Psychology, 2019)
In breast cancer patients, quality of life has been associated with treatment response and overall survival. One hundred women undergoing chemotherapy treatment for breast cancer completed questionnaires including demographic and clinical information, the EORTC-Quality of Life Questionnaire, Hospital Anxiety and Depression Scales, Body Image Scale, Index of Family Relations and the Life Orientation Test. The results showed that higher optimism and better body image were associated with improved quality of life. Distress significantly predicted physical and emotional quality of life, but recurrence only predicted physical quality of life. Family stress was a moderator in the relationship between psychological distress and emotional quality of life, showing the need to screen and intervene on family stress in patients with breast cancer. The results may help in designing interventions for women with breast cancer in order to promote quality of life.